Evolutionary history of genus Coptis and its dynamic changes in the potential suitable distribution area - Wang, Yiheng; Sun, Jiahui; Qiao, Ping; Wang, Jingyi; Wang, Mengli; Du, Yongxi; Xiong, Feng; Luo, Jun; Yuan, Qingjun; Dong, Wenpan; Huang, Luqi; Guo, Lanping (Frontiers in Plant Science, 2022)
The genus Coptis belongs to the Ranunculaceae family, containing 15 recognized species highly diverse in morphology. It is a conspicuous taxon with special evolutionary position, distribution pattern and medicinal value, which makes it to be of great research and conservation significance. In order to better understand the evolutionary dynamics of Coptis and promote more practical conservation measures, we performed plastome sequencing and used the sequencing data in combination with worldwide occurrence data of Coptis to estimate genetic diversity and divergence times, rebuild biogeographic history and predict its potential suitable distribution area. The average nucleotide diversity of Coptis was 0.0067 and the hotspot regions with the highest hypermutation levels were located in the ycf1 gene. Coptis is most likely to have originated in North America and Japanese archipelago and has a typical Eastern Asian and North American disjunct distribution pattern, while the species diversity center is located in Mid-West China and Japan. The crown age of the genus is estimated at around 8.49 Mya. The most suitable climatic conditions for Coptis were as follows: precipitation of driest quarter > 25.5 mm, annual precipitation > 844.9 mm and annual mean temperature -3.1 to 19 ℃. The global and China suitable area shows an upward trend in the future when emission of greenhouse gases is well controlled, but the area, especially in China, decreases significantly without greenhouse gas policy interventions. The results of this study provide a comprehensive insight into the Coptis evolutionary dynamics and will facilitate future conservation efforts.